2019
DOI: 10.1128/jvi.00469-19
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Nonstructural Protein 1 Beta Interacts with Nucleoporin 62 To Promote Viral Replication and Immune Evasion

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) blocks host mRNA nuclear export to the cytoplasm, and nonstructural protein 1 beta (nsp1␤) of PRRSV has been identified as the protein that disintegrates the nuclear pore complex. In the present study, the molecular basis for the inhibition of host mRNA nuclear export was investigated. Nucleoporin 62 (Nup62) was found to bind to nsp1␤, and the region representing the C-terminal residues 328 to 522 of Nup62 was determined to be the binding domain for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…This activity is known to be associated with coronavirus nsp1, which inhibits nuclear export by interacting with the nuclear export factor NXF1 in SARS-CoV or the nuclear pore complex component Nup93 in SARS-CoV-2 [111,112] . Similarly, PRRSV nsp1β causes imprisonment of host mRNAs in the nucleus, by binding Nup62 to cause the disintegration of the nuclear pore complex 113,114 . This inhibition of host mRNA nuclear export has been found to reduce synthesis of interferon-stimulated genes 114 , and mutations in nsp1β which ablate this activity lead to reduced viral load and increased neutralising antibody titres in pigs 115 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This activity is known to be associated with coronavirus nsp1, which inhibits nuclear export by interacting with the nuclear export factor NXF1 in SARS-CoV or the nuclear pore complex component Nup93 in SARS-CoV-2 [111,112] . Similarly, PRRSV nsp1β causes imprisonment of host mRNAs in the nucleus, by binding Nup62 to cause the disintegration of the nuclear pore complex 113,114 . This inhibition of host mRNA nuclear export has been found to reduce synthesis of interferon-stimulated genes 114 , and mutations in nsp1β which ablate this activity lead to reduced viral load and increased neutralising antibody titres in pigs 115 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PRRSV nsp1β causes imprisonment of host mRNAs in the nucleus, by binding Nup62 to cause the disintegration of the nuclear pore complex 113,114 . This inhibition of host mRNA nuclear export has been found to reduce synthesis of interferon-stimulated genes 114 , and mutations in nsp1β which ablate this activity lead to reduced viral load and increased neutralising antibody titres in pigs 115 . These findings suggest that nsp1β-mediated nuclear export inhibition may be responsible for the translational repression seen in our host differential gene expression analyses, which, analogously to conclusions drawn for SARS-CoV-2 [109,110] , may be a key mechanism by which PRRSV evades the host response to infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the abovementioned host factors, other cellular components are also involved in interacting with PRRSV. The cellular protein nucleoporin 62 (Nup62) interacts with nsp1β, leading to inhibition of host antiviral protein expression, revealing a new strategy of immune escape [ 47 ]. In addition, research found that cellular retinoblastoma protein (pRb) interacts with the nsp9 of genotype 2 PRRSV, which will benefit the replication of PRRSV-2 [ 49 ].…”
Section: The Prrsv–host Interactionsmentioning
confidence: 99%
“…Numerous host factors have been reported as either facilitating or suppressing virus infection and/or replication. These factors encompass cell surface receptors for PRRSV infection such as CD163, sialoadhesin, heparin sulfate, vimentin, CD151, and CD209 [24] and other cellular factors such as MYH9 [25], heparinase [26], CH25H [27,28], nucleoporin 62 [29], annexin A2 [30], ZAP [31], DHX36 [32], and so forth. Likewise, studies from our laboratory show that membrane proteins including MOV10, galectin-1, and galectin-3 can influence the replication of PRRSV [33][34][35].…”
Section: Introductionmentioning
confidence: 99%